A Living 3D In Vitro Neuronal Network Cultured inside Hollow Electrospun Microfibers. Issue 5 (12th March 2018) - Wu, Yingjie; Ranjan, Vivek Damodar; Zhang, Yilei
Abstract: Micro/nanofiber‐based scaffolds are widely used as a physical graft for axon growth in vitro for nerve tissue engineering. In this study, the fabrication of hollow coaxial microfibers with a 3D structure for directional neuronal cell culture is reported. The coaxial microfibers with poly‐ε‐caprolactone (PCL) sheath and polyvinyl alcohol (PVA) mixed with PC 12 cells as core are prepared using a coaxial double cylinder based on the liquid–liquid coflowing electrospinning method. By optimizing the electrospinning conditions, uniform microfibers with an average diameter of 54.6 µm are obtained using a PCL concentration of 20% and a tip‐to‐collector distance of 6 cm with a voltage of 6 kV. After selectively dissolving the PVA core, pheochromocytoma 12 (PC12) cells are successfully cultured inside these fibers. It is experimentally confirmed that such 3D hollow fibers can support and guide PC12 cells to grow, proliferate, and differentiate inside the hollow fibers and form 3D‐connected neuronal networks with axons extended along the hollow fibers. This implies that complex nerve connection could be constructed using the low cost and powerful liquid–liquid coflowing electrospinning method, which open the door to culture well‐controlled nerve connections as in vitro models for neural tissue regeneration, brain disease models, and so on. Abstract : A core–shell microfiber system for building living 3D cell‐culture model is successfully developed. The hollow coaxial poly‐ε‐caprolactone/polyvinyl alcohol (PVA) microfibers encapsulated with PC12 cells are fabricated by electrospinning method. After selectively dissolving the PVA core, pheochromocytoma 12 cells with survival, proliferation, and differentiation inside these fibrin matrices form functional 3D‐ connected functional neuronal networks.